2012
DOI: 10.1136/gutjnl-2011-301116
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immunity suppresses formation and progression of diethylnitrosamine-induced liver cancer

Abstract: Background Hepatocellular carcinoma (HCC) is a typical inflammation-associated cancer, but may also provoke antitumour immune responses whose significance and underlying mechanisms are incompletely understood. Objective To characterise immune responses in the diethylnitrosamine (DEN)-liver cancer mouse model. Design Tumour development and immune cell functions upon DEN treatment were compared between C57BL/6 wild-type (WT), chemokine scavenging receptor D6-deficient, B cell- (Igh6), CD4 T cell- (MHC-II) and T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 54 publications
5
152
0
1
Order By: Relevance
“…5a,c). At this short time after DEN treatment, in agreement with previous data (Schneider et al, 2012), proliferation was essentially observed in nonparenchymal cells. Despite a higher degree of cell proliferation in Ct-HBx-transgenic mice than in either FL-HBxtransgenic or WT mice, no statistical difference was observed (Fig.…”
Section: Effect Of Hbx Expression On Den-induced Initiation Of Carcinsupporting
confidence: 81%
“…5a,c). At this short time after DEN treatment, in agreement with previous data (Schneider et al, 2012), proliferation was essentially observed in nonparenchymal cells. Despite a higher degree of cell proliferation in Ct-HBx-transgenic mice than in either FL-HBxtransgenic or WT mice, no statistical difference was observed (Fig.…”
Section: Effect Of Hbx Expression On Den-induced Initiation Of Carcinsupporting
confidence: 81%
“…Combined, the above results illustrate the necessity of the presence of pro-inflammatory Kupffer cells in the liver at the early stages of chemically induced hepatocarcinogenesis. Especially tissue-resident KC, but not recruited monocyte-derived cells, might be needed in the DEN model, since tumor incidence and growth are unaltered in livers of DEN-treated D6-deficient mice, which are heavily infiltrated by monocyte-derived macrophages[170].Once a primary tumor is established, macrophages can further contribute to HCC progression, although the distinction between KC and monocyte-derived macrophages has not been made in most studies. One study reports a reduced presence of KC -defined as CD68 + cells present in the blood space of cancerous tissue or in the sinusoids of noncancerous tissues -in HCC tissue compared to noncancerous tissue from the same livers and a further decrease of intratumoral KC presence as tumor size increases, suggesting…”
mentioning
confidence: 96%
“…Tumor-associated macrophages (TAMs) and T cells have most frequently been reported in promoting liver cancer [76]. Although the former integrate functionally diverse macrophage subpopulations mediating both pro-and anti-tumorigenic activities, myeloid cells in general predominantly exert pro-tumorigenic activities.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%